If it's not what You are looking for type in the equation solver your own equation and let us solve it.
38-(2x+5)=2(x+9)+x
We move all terms to the left:
38-(2x+5)-(2(x+9)+x)=0
We get rid of parentheses
-2x-(2(x+9)+x)-5+38=0
We calculate terms in parentheses: -(2(x+9)+x), so:We add all the numbers together, and all the variables
2(x+9)+x
We add all the numbers together, and all the variables
x+2(x+9)
We multiply parentheses
x+2x+18
We add all the numbers together, and all the variables
3x+18
Back to the equation:
-(3x+18)
-2x-(3x+18)+33=0
We get rid of parentheses
-2x-3x-18+33=0
We add all the numbers together, and all the variables
-5x+15=0
We move all terms containing x to the left, all other terms to the right
-5x=-15
x=-15/-5
x=+3
| -2a+5a=0 | | 762e-1)-3=6+6e | | 6.8=1.4-0.7y | | x/3-13=-7 | | x/3-13=-1 | | 3(2x+1)+2x=-x+3(3x+1) | | -5=5-4k+2 | | 6x+7-9x=14-15x+12x-7 | | 1=n-3-2n | | 10+n=50 | | -10=m+19 | | 25/x+1=4/5 | | 5x-16=4x+8 | | 107+55+(4-2x)=180 | | 11x-3x(x-2)=8x+3 | | -12=d/7 | | 245=50+(20+9)w | | -27+x=x+10 | | 3(8s+5)-15s=3(3s+4)-15 | | 1/9(t-7)=-8 | | 3y+6+4y-y=-7 | | f(22-9)=119 | | 6n-12+4n=8 | | 6–(2x+3)–4x=6 | | n–11=24–9n | | 8-3r=r-4(2+3r) | | 14u=5u+72 | | -2(8x-1)=5(1-3x) | | 10(h-1)-1=76 | | 16=n+4-5n | | -1.2815=x-11/1.2 | | 21=x/5 |